2022
DOI: 10.3389/fphys.2022.893925
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion diffusion-weighted imaging and shear wave elastography for evaluating peritumoral liver fibrosis after transarterial chemoembolization in a VX2 rabbit liver tumor model

Abstract: In this study, we sought to evaluate changes in peritumoral fibrosis after transarterial chemoembolization (TACE) in a rabbit VX2 liver tumor model using intravoxel incoherent motion diffusion-weighted imaging (IVIM DWI) and ultrasound shear wave elastography (SWE). A total of 20 rabbits underwent implantation of VX2 tumor tissues in the left lobe of the liver. The rabbits were randomly divided into an experimental group (n = 10) or a control group (n = 10). Those in the experimental group were treated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…As a biexponential model for separately assessing the true molecular diffusion and microcirculation perfusion [ 32 ], IVIM has been used to evaluated liver cirrhosis [ 33 ] or fibrosis [ 34 ], as well as for characterizing focal liver lesions [ 35 ]. In our study, we found that there was no statistical significance for D* among varying fibrosis stages ( P = 0.586).…”
Section: Discussionmentioning
confidence: 99%
“…As a biexponential model for separately assessing the true molecular diffusion and microcirculation perfusion [ 32 ], IVIM has been used to evaluated liver cirrhosis [ 33 ] or fibrosis [ 34 ], as well as for characterizing focal liver lesions [ 35 ]. In our study, we found that there was no statistical significance for D* among varying fibrosis stages ( P = 0.586).…”
Section: Discussionmentioning
confidence: 99%
“…All animals underwent either the control or experimental procedure 2 to 3 weeks after tumor implantation, once a welldelineated solitary tumor (1.5-2.0 cm in diameter) could be detected on ultrasound images (18,19). For these procedures, anesthesia was administered at a concentration of 2.5% to 3.5%, with an oxygen flow rate of 1 L/min.…”
Section: Experimental and Control Proceduresmentioning
confidence: 99%
“…Each rabbit was placed on an operating table Erlangen, Germany). The procedure was then performed under fluoroscopic guidance as described in a previous study (19). Briefly, the right femoral artery was selected and punctured with a 20G blood vessel puncture needle.…”
Section: Experimental and Control Proceduresmentioning
confidence: 99%
See 1 more Smart Citation